Reported adverse events following COVID-19 vaccination in gynecologic cancer patients in Thailand: A descriptive study - Sasivimon Ratree; Nicha Assavapokee; Somsook Santibenchakul; Nakarin Sirisabya; Waranyoo Phoolcharoen; Natacha Phoolcharoen (PLoS ONE, 2026)
Objective Data on the safety of coronavirus disease 19 (COVID-19) vaccines in gynecologic cancer patients are scarce. The type of vaccine used in Thailand differs from what has been studied in other countries. This study evaluated the prevalence and characteristics of reported adverse events following COVID-19 vaccines in patients with gynecologic cancer patients. Method A retrospective, single-center descriptive study was performed in patients with gynecologic cancer who received at least one dose of the COVID-19 vaccine at King Chulalongkorn Memorial Hospital, Thailand, from January 2020 to August 2021. Adverse events were collected through structured telephone interviews using a standardized questionnaire. Descriptive statistics summarized patient characteristics and adverse events. Associations with any-grade adverse events were assessed using logistic regression and Fisher’s exact test for categorical variables. Results Of the 294 patients interviewed, 72.8% were in remission, under surveillance, or in palliative treatment at the time of vaccination, and 17.7% were undergoing treatment. The most common adverse effects were grade 1–2 injection site reactions. One patient developed grade 3 fever and seizures 10 days after the first dose of the AstraZeneca vaccine. Between the second and fourth doses of the vaccination, the most common adverse events were grade 1–2 injection site reactions. No severe allergic reactions or grade 4 adverse events were reported. The study concluded that patients under 60 years of age had more adverse events than older patients (adjusted odds ratio 1.99, 95% confidence interval 1.08–3.71 p = 0.029). The treatment status did not affect adverse events. Of 283 patients who received two doses, 27.6% were infected with COVID-19. Conclusion COVID-19 vaccination was generally well tolerated among gynecological cancer patients who received active anticancer therapy and those under surveillance. Younger patients frequently reported more adverse effects than older patients.